Valve mediated hemodynamics and their association with distal ascending aortic diameter in bicuspid aortic valve subjects. Issue 1 (8th April 2017) - Raghav, Vrishank; Barker, Alex J.; Mangiameli, Daniel; Mirabella, Lucia; Markl, Michael; Yoganathan, Ajit P.
Abstract : Purpose: Valve mediated hemodynamics have been postulated to contribute to pathology of the ascending aorta (AAo). The objective of this study is to assess the association of aortic valve morphology and hemodynamics with downstream AAo size in subjects with bicuspid aortic valve (BAV) disease. Materials and Methods: Four‐dimensional flow MRI at 1.5 or 3 Tesla was used to evaluate the hemodynamics in the proximal AAo of 52 subjects: size‐matched controls with tricuspid aortic valves (n = 24, mid ascending aorta [MAA] diameter = 38.0 ± 4.9 mm) and BAV patients with aortic dilatation (n = 14 right and left coronary leaflet fusion [RL]‐BAV, MAA diameter = 38.1 ± 5.3 mm; n = 14 right and noncoronary leaflet fusion [RN]‐BAV, MAA diameter = 36.5 ± 6.6 mm). A validated semi‐automated technique was used to evaluate hemodynamic metrics (flow angle, flow displacement, and jet quadrant) and valve morphology (orifice circularity) for all subjects. Regression analysis of these metrics to AAo diameter was performed. Results: RN‐BAV subjects displayed a stronger correlation between hemodynamic metrics in the proximal AAo with diameter in the distal AAo compared with size‐matched tricuspid aortic valve (TAV) controls and RL‐BAV subjects. The distal AAo diameter was found to be strongly correlated to the upstream flow displacement (R 2 adjusted = 0.75) and flow angle (R 2 adjusted = 0.66) measured at the sino‐tubular junction (STJ). Orifice circularity was also strongly correlated (R 2 adjusted = 0.53) to the distal AAo diameter in RN‐BAV subjects. For TAV controls and RL‐BAV subjects, correlations were weaker (R 2 adjusted < 0.2). Conclusion: Hemodynamics in the STJ were strongly correlated to the distal AAo diameter for the RN‐BAV subjects. Hemodynamic metrics were more strongly correlated to the downstream aortic size when compared with valve morphology metrics. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:246–254.